PEMANFAATAN SEMAK BUNGA PUTIH (Chromolaena odorata) SEBAGAI PAKAN LOKAL SUMBER PROTEIN UNTUK TERNAK SAPI: KONSUMSI, DAYA CERNA DAN FERMENTASI RUMEN - Mulik, Marthen L.; Jelantik, I Gusti; Mulik, Yelly M; Dahlanuddin, Dahlanuddin; Wirawan, I G. Oka; Permana, Bambang (Pastura, 2015)
Chromolaena odorata (CO) contains high protein (21-36%) and has the potency to be utilized as a cheap protein source for livestock due to its abundants availability. However, it also contain secondary metabolic compounds that could has a negative effects on livestock, hence it requires treatments to eliminate the antinutrient compounds. One of the methods is pelleting. This experiment aimed at assessing the efficacy of chromolaena level in pelleted ration for fattened cattle. Four bali young male aged ± 2 years old were allotted into four dietary treatments in a latin square experimental design. The treatments were pellet contains CO at a level of 10% (COP10) or 20% (COP20), or 30% (COP30) or 40% (COP40). The pellet was offered at 2% live weight (LW), and kume grass hay was provided ad libitum as basal diet. The pellet was iso energy (11.5 MJ ME/kg DM) and nitrogenous (20% CP). Parameters measured were dietary intake and digestibility, rumen fermentation, and rumen microbial protein production. The results showed that increasing level of chromolaena to 40% in the pellet significantly surpressed most of the measured parameters. Dry matter intake declined from 2.5% LW in treatment COP10 to 2.19% LW in COP40. Similarly, crude protein intake reduced from 749 g/d (COP10) to 661 g/d (COP40). Unaffected parameters were digestibility, rumen ammonia concentration (116-125 mg/dL),total VFA, and efficiency of rumen microbial protein synthesis (60,4-73,4 g/kg BOT). It is concluded that chromolaena can be utilized as protein source for ruminants, yet it tends to depress intake at high level of inclusion (40%). On the other hand, dietary digestibility and rumen function were not effected by level of chromolaean, though efficiency of rumen microbial protein synthesis was lower than the recommended values in the exisiting feeding standards. Therefore, further research is warrant to devise appriate treatments to improve feeding value of chromolaena as cheap protein source for livestock. Key words: Chromolaeana odorata, protein, intake, rumen microbial protein, cattle